Conciliation as an essential method for the amicable settlement of collective labour disputes in accordance with law 90/02 of 1990 - Rikli, Seddik (Journal of Human Sciences, 2023)
The study of the settlement of collective labor disputes is of great importance at more than one economic, social and political level in view of the damage and consequences that these disputes can cause and which can go as far as slowing down the national economy, and threaten professional stability and social peace, when they are spread over time and according to the importance of the sector concerned. In order to deal with it, the legislator, in various countries, has taken appropriate measures through the adoption of a set of means of settling such conflicts.In this context, conciliation is one of the main modes of amicable settlement of collective disputes provided for by law 90/02 of 1990, so we will study it analytically in order to highlight the main bases of its regime. legal, in terms of composition, operation and procedures, function, powers attributed to it and limits in the light of the economic, social and political orientations that Algeria has known since the promulgation of the Constitution of 23 February 1989.